2020
DOI: 10.21037/apm-20-387
|View full text |Cite
|
Sign up to set email alerts
|

Naoluo Xintong capsule ameliorates apoptosis induced by endoplasmic reticulum stress in rats with cerebral ischemia/ reperfusion injury

Abstract: Background: Naoluo Xintong (NLXT) capsuleis a newly developed drug recorded in the Chinese Pharmacopoeia. It is derived from traditional Chinese medicine (TCM) NLXT decoction, and has been widely used to treat cerebrovascular diseases in clinic. However, it is currently unknown whether it improve cerebral ischemia reperfusion (I/R) injury. Methods:The effect of NLXT on regional cerebral blood flow (rCBF) was examined using Laser Doppler flower. The Terminal deoxyribonucleotide transferase-mediated Nick end lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…We speculate that electroacupuncture may inhibit neuroin ammation and promote nerve function repair in ischemic stroke. Studies have shown that microglia are activated after cerebral ischemia, producing large amounts of neurotoxic molecules and pro-in ammatory cytokines that exacerbate brain damage [13][14][15][16][17]. Because of their prevalence in the central nervous system, NLRP3 in ammatory vesicles are highly concerned [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that electroacupuncture may inhibit neuroin ammation and promote nerve function repair in ischemic stroke. Studies have shown that microglia are activated after cerebral ischemia, producing large amounts of neurotoxic molecules and pro-in ammatory cytokines that exacerbate brain damage [13][14][15][16][17]. Because of their prevalence in the central nervous system, NLRP3 in ammatory vesicles are highly concerned [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Caspase 12 belongs to the conserved caspase family, which is present on the cytoplasmic surface of the ER. It has been demonstrated that the activation of caspase 12 is essential for ERS-induced apoptosis, and non-ERS-mediated apoptosis does not involve activation of caspase 12 [37][38][39]. When ERS occurs, Ca 2+ release activates procaspase 12 into caspase 12 and subsequently activates caspase 9 and caspase 3, which leads to an apoptotic caspase cascade [40].…”
Section: Discussionmentioning
confidence: 99%
“…It could also reduce the expression of caspase-12 within 24 hours of CIRI, ultimately improve CIRI. [117]…”
Section: The Role Of the Tcm For Blood Circulation And Stasis Removal...mentioning
confidence: 99%
“…It could also reduce the expression of caspase-12 within 24 hours of CIRI, ultimately improve CIRI. [117] For the effects on cell proliferation and differentiation, Naoluo Xintong Decoction not only facilitates the mRNA expression of SOCS5, but also restrains the level of prolactin receptor and the JAK/STAT pathway. Thus, Naoluo Xintong Decoction promotes the differentiation of neural stem cells into neurons and their migration.…”
Section: Ciri Targets the Jak/stat Pathway To Boost Cell Proliferatio...mentioning
confidence: 99%